1983
DOI: 10.1002/ijc.2910310609
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of epstein‐barr virus‐specific T‐cell immunity in malaria‐endemic and ‐nonendemic regions of Papua New Guinea

Abstract: Epstein-Barr virus genome-positive Burkitt's lymphoma is endemic in Africa and Papua New Guinea and in both countries the tumour is restricted to regions with holoendemic malaria. The present work has compared groups of healthy indigenous individuals living in malarious and non-malarious regions of Papua New Guinea for Epstein-Barr virus-specific T-cell-mediated immunity using the in vitro regression assay. Residents of the malarious region (55 tested), when compared with either residents of the non-malarious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 22 publications
4
45
0
Order By: Relevance
“…Such immunologic perturbations within the EBV-specific CD8 ϩ T-cell compartment could predispose to the functional deficits that accompany eBL (46). Second, our study addresses the long-standing question of whether eBL is associated with a generalized, malaria-induced suppression of T-cell immunity (21,22,47). Our data demonstrate that EBV-specific, but not CMV-specific or total, CD8 ϩ T-cell populations show significant differences associated with malaria exposure.…”
Section: Interestingly Cd8mentioning
confidence: 72%
See 1 more Smart Citation
“…Such immunologic perturbations within the EBV-specific CD8 ϩ T-cell compartment could predispose to the functional deficits that accompany eBL (46). Second, our study addresses the long-standing question of whether eBL is associated with a generalized, malaria-induced suppression of T-cell immunity (21,22,47). Our data demonstrate that EBV-specific, but not CMV-specific or total, CD8 ϩ T-cell populations show significant differences associated with malaria exposure.…”
Section: Interestingly Cd8mentioning
confidence: 72%
“…Indeed, these properties underlie the hypothesis that P. falciparum malaria suppresses immunity to EBV during coinfection. In the early 1980s, a series of seminal studies demonstrated that lymphocytes from malaria-infected individuals were unable to control the proliferation of EBV-transformed B cells in relatively crude regression assays (21,22). Although these observations suggest that P. falciparum malaria infection disrupts EBV-specific immunity, the effector cells or mediators responsible for controlling EBV-infected B-cell growth were not identified, and overall immune competence was not assessed in the small number of individuals studied.…”
mentioning
confidence: 99%
“…The initial HLA screening was performed by fluorescence-activated cell sorter (FACS) analysis using the HLA B*0801 monoclonal antibody (clone 59HA-1; One Lambda Inc.) and was later confirmed by full class I tissue typing (Princess Alexandra Hospital tissue typing facility, Brisbane, Australia). Serological testing for EBV capsid antibody (VCA) was initially done by immunofluorescence microscopy (37) and later confirmed by enzyme-linked immunosorbent assay specific for VCA immunoglobulin G (IgG) and IgM and EBNA IgG (Queensland Medical Laboratory, Brisbane, Queensland, Australia). The inclusion criteria for the trial were EBV-seronegative and HLA B*0801-positive status.…”
Section: Methodsmentioning
confidence: 99%
“…Holoendemic malarial infection is thought to facilitate this oncogenic process. Therefore, BL occurs with increased incidence rate in children in Sub-Saharan Africa (3), in South America (4), and in Papua New Guinea (5). In addition, BL is increased in AIDS patients (6 -8).…”
mentioning
confidence: 99%